PERAN PERTANIAN DI INDONESIA DALAM MEMASUKI PERDAGANGAN INTERNASIONAL - Mhd. Faisal Anwar Afandi Rambe; Nuri Aslami (Journal of Social Research, 2022)
Trade on Agriculture has been reformed since January 1995. ft was a result of Uruguay Round and stated on Agreement on Agriculture. However, its implementations hove given negative aspects to developing countries. It was caused by the malfunction of specific protection mechanism. Besides, special and differential treatment, created by developed countries, is not implemented effectively. Accordingly, sector on Agriculture has been being negotiated since the Doha Round in 2001